An analytical study at the General Company for the manufacture of batteries - محمد, بشرى عباس (Journal of Economics and Administrative Sciences, 2015)
This study carry’s out the correlation and the effect of two main variables, these variables are Job Satisfaction included six sub: wages - salaries and justice and yield, working  conditions    and services, pattern of supervision and the relationship with the manger, Relationship with colleagues, the content of the work and the variety of tasks, development and  promotion  opportunities available  to  an individual,   and Organizational Performance included  two sub variables:  Efficiency, Effectiveness.  This research was conducted using a questioner as a main tool, This questioner was distributed randomly to a research community composed of seventy three working staff at the State Company for Batteries Industries, Resolution allocated two types of information included the first introductory general information about the study sample and the second related variables, the study included forty-six questions.The study used a number of means for the purpose of statistical analysis of the data based on the statistical program SPSS.20.    The most prominent finding at this study was the positive correlation between Job Satisfaction and Organizational Performance. Job Satisfaction affects Organizational Performance.    In the other hand there was another vital finding at this study which is   Job Satisfaction for the working staff was moderate.     Moreover, this study recommends the necessary of the decision makers or high level staff would increase their knowledge to their following staff and make sure they are involved in specialized truing and symposiums, for them to follow up with the latest in Job Satisfaction and its impact on Organizational Performance.    To conduct these results it requires that the leadership believes in the important effect of Job Satisfaction.